Quality of life in patients submitted to radical prostatectomy - Débora Moura Miranda Goluart; Mário Alfredo Silveira Miranzi; Paulo Eduardo Nunes Goulart (Universidade Federal de Goias, 2014)
A cross-sectional study with a descriptive analysis of 81 patients submitted to radical prostatectomy (RP). Our objective was to correlate quality of life (QL) according to the EORTC-QLQ C30 with age group and time after surgery. Mean age was 65.7 years. Most sought the care of urology, asymptomatic. Some referred former smoking (49.9%) and high blood pressure (53.1%). Mean preoperative SBP was 8.4 ng/ml. Most participants were in stages T2c to T3, Gleason ?6 and over a year after surgery. Erectile dysfunction presented in 90.1%, and urinary incontinence in 33.3%. Functional and overall health scales presented high QL indexes, and symptomatology, with low ones. Older adults presented higher QL regarding emotional functioning, financial difficulties and overall health, as well as those with over a year after surgery, regarding cognitive functioning and fatigue. Although QL was not greatly affected, there were differences between age groups and time after surgery. doi: 10.5216/ree.v16i3.21589.